Photovoltaic device based on TiO2 rutile/anatase phase junctions fabricated in coaxial nanorod arrays. (July 2015) - Yan, Pengli; Wang, Xiang; Zheng, Xiaojia; Li, Rengui; Han, Jingfeng; Shi, Jingying; Li, Ailong; Gan, Yang; Li, Can
Abstract: Phase-junctions formed in mixed crystalline phases of semiconductor based photocatalysts (TiO2 and Ga2 O3 ) shows enhanced photocatalytic activity owing to efficient separation of photogenerated charges. However, the phase junction effect on charge separation has not been directly verified yet. In this study, we fabricated a prototype photovoltaic device based on TiO2 rutile/anatase coaxial nanorod arrays (NRAs) to demonstrate charge separation at the interface of polymorphic crystal phases. The device—FTO/rutile NRAs/anatase/ITO shows an ordinary photovoltaic response (open-circuit voltage V oc : 154 mV, short-circuit current density J sc : 1.76 mA/cm 2 ), contrasting with photo resistor behavior of two TiO2 single phase devices of core–core (FTO/rutile NRAs/ITO) and shell–shell (FTO/anatase/ITO). Experimental evidences suggest that the built-in electric field at the interface of rutile/anatase phase junctions in the FTO/rutile NRAs/anatase/ITO device provides the direct driving force for efficient separation of photogenerated charges. The demonstrated strategy of fabricating phase-junction photovoltaic devices may inspire further investigations on new device converting solar into electrical energy and highlight the key role of the phase junction interface in the properties of the mix-phase photocatalysts. Graphical abstract: Highlights: A prototype PV device based on TiO2 rutile/anatase coaxial nanorod was fabricated. The TiO2 phase junction PV device shows a V oc of 154 mV and J sc of 1.76 mA/cm 2 . The single phase device—FTO/rutile NRAs (or anatase)/ITO act as photo resistor. Charge transfer between the rutile/anatase is detected from the external circuit.